Case Report Cognitive impairment in elderly population is not always a dementia - Narejko, Karolina; Niemczuk, Martyna; Lech, Maksymilian Adam; Koziej, Sylwia; Kasiukiewicz, Agnieszka; Wojszel, Zyta Beata (Journal of Education, Health and Sport, 2025)
INTRODUCTION AND AIM Cognitive impairment is frequent disease in elderly people, prompting to the suspection of dementia. Considering the multi-disease nature and complexity of the treatment process for the geriatric population, it is crucial to exclude the several other disease processes and to actively search for causes of cognitive impairment, especially reversible conditions whose treatment can significantly improve cognitive function. DESCRIPTION OF THE CASE An 89-year-old man was admitted to the Geriatrics Unit due to progressive cognitive impairment and motor signs with the suspected dementia diagnosis. After a broad physical examination, laboratory tests and neuroimaging, the brain tumor was detected. The treatment included antiedematous drugs- Mannitol and Dexamethasone. The treatment resulted in an improvement of the contact with the patient and his general condition. CONCLUSION This clinical case demonstrates the relevance of searching for less common causes of cognitive impairment, as well as the necessity of careful investigation of concomitant coexisting symptoms, which can often lead us to the right diagnosis .